Error Analysis in Using Chinese Words “Qiwang期望” and “Yuanwang愿望” of STBA-PIA Second Year Student 2019/2020 Academic Year - Yenny Marlim (Journal of Language, Literature and Teaching, 2021)
The purpose of this research is to understand the error types and the error causes of Sekolah Tinggi Bahasa Asing Persahabatan Internasional Asia (STBA-PIA) second year students in using the Chinese words “Qiwang期望” and “Yuanwang愿望”. The design of this research is a descriptive qualitative and using both elicitation and interview methods for data collection. Picture description and elicited imitation methods are applied as the instruments used for describing the error types in using the Chinese words “Qiwang期望” and “Yuanwang愿望”, while interview method is used in defining the causes of errors occurred in using the Chinese words “Qiwang期望” and “Yuanwang愿望”. The results of this study show that there are four types of errors occured in using Chinese words “Qiwang期望” and “Yuanwang愿望” by STBA-PIA second year students which are error of addition (14.6%), error of substitution (66.5%), error of order (12.6%) and error of omission (6.3%). The results also show that there are two types of error causes, they are interlingual transfer (51.7%) and intralingual transfer (48.3%) in which the intralingual transfer includes the overgeneralization (17.2%), ignore of rule restriction (13.8%), incomplete application of rules (10.3%) and false concept hypothesized (7%).Keywords: Error, Chinese Word, 期望(qiwang), 愿望(yuanwang)